Optimizing Small Wind Turbine Blades: A BEMT Approach Optimizing Small Wind Turbine Blades: A BEMT Approach - Tshepo Sithole; Lukas W. Snyman; Vasudeva R. Veeredhi; Thembelani Sithebe (International Journal of Energetica)
This paper explores the optimization of small wind turbine blades, focusing on the design and utilization of theoretical algorithms such as computational fluid dynamics (CFD), blade elementary method (BEM) theory, and the vortex wake system (VWS). Among these methods, BEM theory has proven to be the most effective in optimizing horizontal-axis wind turbine (HAWT) blades and is commonly employed in modeling and constructing small wind turbine blades. The study centers on designing and optimizing aerofoils to enhance rotor blade pitch angles and determining the optimal number of blades for maximizing power output at various wind speeds using BEMT. Using a NACA-4412 type aerofoil as the starting point, the paper investigates different pitch angles, blade radii, and chord lengths for Designs 1, 2, and 3. Results indicate that at an average wind speed of 0 - 2.3 m/s (8.28 km/h), 3-blade, 5-blade, and 7-blade sets were designed and optimized for performance. The predictions suggest rated outputs of 7.5 W, 20 W, and 40 W for Designs 1, 2, and 3, respectively. The study reveals that Design 3, with a blade radius of 1m, a chord length of 0.1m, and a pitch angle ranging from 12° near the rotor hub to 2° at the blade radius tip, achieved a significant power output of 39.5 W at a wind speed of 4.2 km/h. The findings contribute valuable insights into optimizing wind turbine blade design for enhanced energy efficiency.